Wireless public safety networks. - Camara, Daniel; Nikaein, Navid (Elsevier, 2015)
Wireless Public Safety Networks, Volume One: Overview and Challenges presents the latest advances in the wireless Public Safety Networks (PSNs) field, the networks established by authorities to either prepare the population for an eminent catastrophe, or as support during crisis and normalization phases. Maintaining communication capabilities in a disaster scenario is crucial for avoiding loss of lives and damages to property. Wireless Public Safety Networks examines past communication failures that have directly contributed to the loss of lives. This book will give readers a broad view of the PSNs field, analyzing the benefits PSNs may bring to society, the main challenges related to the establishment and maintenance of these networks, the latest advancements in the field, and future perspectives.